Luminescent crystals and their manufacture
A top-down method for manufacturing luminescent crystals using liquid phase dispersion and ball milling stabilizes and reduces solid materials to achieve high quantum yield and cost-effective scalability for diverse applications.
Patent Information
- Application Number
- JP2023114328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2015-07-31
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2036-05-25
AI Technical Summary
Existing methods for manufacturing luminescent crystals, particularly quantum dots, are difficult to control, scale up, and produce non-stoichiometric reactions with high by-product formation, making them commercially unattractive and expensive.
A top-down method involving the dispersion of solid materials in a liquid phase with surfactants and optionally prepolymers, using ball milling and low-boiling solvents to stabilize and reduce the size of luminescent crystals to 2-50 nm, achieving narrow size distribution and high quantum yield.
The method produces luminescent crystals with excellent optical properties, reduced material requirements, lower costs, and ease of scalability, suitable for various applications including electronic and optical devices.
Smart Images

Figure 0007617986000004 
Figure 0007617986000005 
Figure 0007617986000006
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of luminescent crystals (LCs), more particularly quantum dots (QDs). The present invention provides methods for producing such luminescent crystals, to compositions comprising luminescent crystals, and to electronic devices, decorative coatings, and intermediates comprising LCs. [Background technology]
[0002] Light-emitting crystals, specifically quantum dots, are a well-known class of materials. Such QDs have many applications in industrial and commercial products, such as electronic devices, e.g., light-emitting diodes or displays.
[0003] Loredana Prodesescu et al. (Nano Lett. 2015, vol. 15, pp. 3692-3696) disclose a novel class of high-quality luminescent quantum dots (QDs). The QDs were synthesized with very high dimensional precision using inexpensive chemicals; the QD diameter was controlled by adjusting the synthesis parameters, such as temperature and reaction time. However, the method was difficult to control (due to the very fast particle growth rate of this material composition) and difficult to scale up, so only very small quantities were synthesized. Furthermore, the reaction is non-stoichiometric, leading to a large amount of by-products. Furthermore, the reaction can only be carried out in a high-boiling solvent such as octadecene (due to the high reaction temperature), which requires a solvent exchange if QDs are required in a low-boiling solvent such as toluene for the final application. This synthesis route is known as the "hot injection method" using standard laboratory equipment. Due to these disadvantages, the synthesis method of QDs is commercially unattractive and makes QDs expensive.
[0004] Pfenninger et al. (WO 2007 / 109734) disclose a similar material, but obtained in the form of a thin film by vacuum deposition. Such a manufacturing method is also considered to be disadvantageous.
[0005] Guo et al. (WO 2014 / 007966) disclose standard luminescent QDs of the core-shell type based on CdSe or InP, which further contain C5-C8 carboxylic acids. Standard CdSe and InP require a larger band gap semiconductor shell (e.g. ZnS) to achieve the desired optical functionality. This additional synthesis step further increases their price, which is disadvantageous for many applications.
[0006] Dandang Zhang et al. (JACS, 2015, pp. 9230-33) disclose the solution-phase synthesis of cesium lead halide perovskite nanowires. Like Prodesescu mentioned above, the literature discloses obtaining the nanowires by hot injection method using standard laboratory equipment. Such nanowires are not quantum dots.
[0007] Kojima Akihiro et al. (JP 2014-078392 A) disclose an electroluminescent device comprising a perovskite compound. Perovskites are obtained by a specific solution process called melt-dissolving. This is a bottom-up method that involves crystallizing the target compound. Such a process is difficult to scale up and difficult to control. Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, the object of the present invention is to alleviate at least some of these shortcomings of the state of the art. In particular, the object of the present invention is to provide an improved method for producing LC / QDs. A further object is to provide new materials comprising LC / QDs suitable for a wide variety of applications, such as electronic and optical devices, and decorative coatings. [Means for solving the problem]
[0009] These objects are achieved by a method according to claim 1, an ink according to claim 9, an intermediate product according to claim 17 and a use according to the claims. Further aspects of the invention are disclosed in the description and the independent claims, and preferred embodiments are disclosed in the description and the dependent claims. The invention relates in particular to a method according to claim 1, an ink according to claim 9, an intermediate product according to claim 17 and a use according to the claims. A method for producing light-emitting crystals, specifically quantum dots (first aspect); A composition in the form of a suspension, also called an "ink" or "prepolymer dispersion", and its uses (second aspect); Solid polymer compositions and uses thereof (third aspect); intermediate goods (fourth aspect); Apparatus such as electronic devices, optical devices, and articles comprising the coated surfaces (fifth aspect); A method for producing a polymer composition (sixth aspect); A method for producing an intermediate product (seventh aspect); and Manufacturing method of the device (eighth aspect) to provide.
[0010] The present invention will be described in detail below. It should be understood that the various embodiments, options, and ranges provided / disclosed herein may be freely combined. Furthermore, depending on the specific embodiment, selected definitions, embodiments, or ranges may not apply.
[0011] As used herein, the following definitions apply unless otherwise stated.
[0012] As used in the context of the present invention, the terms "a," "an," "the," and similar terms are intended to encompass both the singular and the plural, unless otherwise stated herein or clearly contradicted by context. Furthermore, the terms "including," "containing," and "comprising" are used herein in their open, non-limiting sense. The term "containing" includes both "comprising" and "consisting of."
[0013] Unless otherwise indicated herein or clearly contradicted by context, percentages are in weight percent.
[0014] The term "luminescent crystal" (LC) is known in the art and refers to 2-50 nm nanocrystals made of semiconductor materials. The term includes quantum dots, which are nanocrystals typically in the range of 3-15 nm, up to 50 nm. Preferably, the luminescent crystals are approximately equiaxed (e.g., spherical or cubic). A particle is considered to be approximately equiaxed if the aspect ratio (longitudinal:shortitudinal) of all three orthogonal dimensions is between 1 and 2.
[0015] The LC, as the term suggests, exhibits luminescence. In the context of the present invention, the luminescent crystal is typically a single crystal particle that is spatially separated from other particles due to the presence of a surfactant. It is a semiconductor material that exhibits a direct band gap (typically in the range of 1.1-3.8 eV, more typically 1.4-3.5 eV, and even more typically 1.7-3.2 eV). In response to illumination with electromagnetic radiation equal to or higher than the band gap, valence band electrons are excited into the conduction band, leaving behind electron holes in the valence band. The formed excitons (electron-electron hole pairs) then radiatively recombine in the form of photoluminescence, with a maximum intensity centered around the LC band gap value and exhibiting a photoluminescence quantum yield of at least 1%. In contact with an external source of electrons and electron holes, the LC can exhibit electroluminescence. In the context of the present invention, the LC does not exhibit mechanoluminescence (e.g., piezoluminescence), chemiluminescence, electrochemiluminescence, or thermoluminescence.
[0016] The term "quantum dot" (QD) is known and specifically refers to semiconductor nanocrystals with diameters typically between 3 and 15 nm. In this range, the physical diameter of the QDs is smaller than the bulk excitation Bohr radius, making quantum confinement effects dominate. As a result, the electronic states of the QDs, and therefore the band gap, are a function of the QD composition and physical diameter, i.e., the absorption / emission color is related to the diameter of the QDs. The optical quality of QD samples is directly related to their homogeneity (more monodisperse QDs have smaller FWHM of emission). When QDs reach diameters larger than the Bohr radius, quantum confinement effects are hindered and the sample may no longer be luminescent, since non-radiative pathways for exciton recombination may become dominant. QDs are therefore a specific subgroup of nanocrystals, specifically defined by their diameter and diameter distribution. The properties of QDs are directly related to these parameters, which distinguish them from nanocrystals.
[0017] The term "solvent" is known in the art and includes, among others, aliphatic hydrocarbons, aromatic hydrocarbons, ethers (such as glycol-ethers), esters, alcohols, and ketones. The above organics may be unsubstituted or substituted with one or more substituents, such as halogen (e.g., fluoro), hydroxy, C1-4 alkoxy (e.g., methoxy or ethoxy), and alkyl (e.g., methyl, ethyl, isopropyl). The above organics include linear, branched, and cyclic derivatives. There may be unsaturated bonds in the molecule. The above compounds typically have 4 to 24 carbon atoms, preferably 5 to 12 carbon atoms, and most preferably 6 to 10 carbon atoms.
[0018] The terms "surfactant", "ligand", "dispersant" and "dispersing agent" are known in the art and have essentially the same meaning. In the context of the present invention, these terms refer to organic substances other than the solvent that are used in suspensions or colloids to improve particle separation and prevent aggregation or precipitation. Without being limited by theory, it is believed that the surfactant physically or chemically attaches to the particle surface before or after the particles are added to the solvent, thereby providing the desired effect. The term "surfactant" includes polymeric materials and small molecules; surfactants typically include polar functional end groups and non-polar end groups. In the context of the present invention, the solvent (e.g., toluene) is not considered a surfactant.
[0019] The term suspension is known and refers to a heterogeneous fluid with a solid internal phase (ip) and a liquid external phase (ep) that contains one or more dispersants / surfactants, optionally one or more solvents, and optionally one or more prepolymers.
[0020] The term "polymer" is known and includes organic and inorganic synthetic materials. The term "prepolymer" includes both monomers and oligomers.
[0021] The term "solution processing" is known in the art and refers to the application of coatings or thin films to substrates using solution-based (=liquid) starting materials. In the context of the present invention, solution processing relates to the manufacture of articles including commercial products, e.g. electronics, optical devices, and (decorative) coatings, as well as intermediates including QD composites or QD layers. Typically, the application of one or more suspensions is carried out at ambient conditions.
[0022] The term "QD composite" refers to a solid inorganic / organic composite material that includes LC / QDs, surfactants, and a matrix. Forms of QD composites include films, fibers, and bulk materials. Because the LC / QDs are not electronically addressed, QD composites are used in applications where the LC / QDs perform only an optical function.
[0023] In QD composites, the LC / QDs are embedded in a matrix, such as a polymer matrix or an inorganic matrix, to spatially separate the LC / QDs from each other. Depending on the application, the thickness of the QD composite film can vary over a wide range, but is typically between 1 and 1000 microns.
[0024] The term "QD layer" refers to a thin layer comprising luminescent crystals (specifically QDs) and surfactants, free or essentially free of further components, e.g. matrix / binders. The QD layer may find various applications, such as quantum dot light emitting diodes (QLEDs), or quantum dot solar cells. In these applications, the LC / QDs are electronically addressed; by applying a voltage, a current flows through the QD layer. Depending on the application, the thickness of the QD layer may vary over a wide range, but is typically between 3 and 200 nm, preferably between 5 and 100 nm, and most preferably between 6 and 30 nm. The QD layer may consist of a monolayer of LC / QDs, and therefore has a thickness equal to the size of the LC / QDs used, thus defining a lower limit of thickness. [Brief description of the drawings]
[0025] The invention is better understood with reference to the figures.
[0026] [Figure 1a] FIG. 1a outlines various aspects of the present invention. [Figure 1b] Figure 1b outlines various aspects of the present invention, in which the x-axis represents particle size and the y-axis represents particle number. [Diagram 2] FIG. 2 shows a TEM image of typical QDs synthesized according to the present invention, indicating the cubic nature of the crystal structure. [Diagram 3] FIG. 3 shows an SEM image of a typical starting solid material powder prepared by precipitation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] In a first aspect, the present invention relates to a method for producing luminescent crystals, in particular from the quantum dot class. More particularly, the present invention relates to a method for producing luminescent crystals with a diameter of 2-50 nm, preferably 3-15 nm, said luminescent crystals being selected from compounds of formula (I), M 1 a M 2 b X c (I) During the ceremony: M 1 represents one or more alkali metals selected from Cs, Rb, K, Na, and Li; M 2 represents one or more metals selected from the group consisting of Ge, Sn, Pb, Sb, and Bi; X represents one or more anions selected from the group consisting of chloride, bromide, iodide, cyanide, thiocyanate, isothiocyanate, and sulfide, and preferably represents one or more halides selected from the group consisting of Cl, Br, and I; a represents 1 to 4; b represents 1 to 2; c represents 3 to 9; The method comprises the steps (a) of providing a solid material, as defined below, and (b) of dispersing said material in the presence of a liquid, as defined below.
[0028] Aspects of the present invention will now be described in further detail.
[0029] LC / QDs are known to be environmentally sensitive materials. First, they tend to aggregate, which induces non-radiative recombination pathways, leading to reduced luminescence quantum yields. Therefore, measures must be taken to stabilize LC / QDs once synthesized. The methods described herein fulfill this need by disclosing improved manufacturing methods that provide LC / QDs in the form of a stable suspension ("ink").
[0030] The method described herein may be considered a "top-down" approach, since the material is first conventionally synthesized, then reduced in size and stabilized to obtain LC / QDs. This method is the opposite of that known and described in Kovalenko (supra), which is a "bottom-up" approach. The method of the invention is further illustrated, but is not limited by, the experiments provided below.
[0031] The method described herein provides LC / QDs with excellent properties. First, small FWHM values (width of emission peak; e.g., 19 nm for emission at 507 nm) are observed. Second, high luminescence quantum yields are observed (e.g., 71% for emission at 507 nm). Thus, the LC / QDs provided by the method of the invention are suitable for many applications in electronic and optical devices. Furthermore, the LC / QDs provided by the method of the invention are also suitable for coating (non-electronic / non-optical) articles, such as decorative coatings.
[0032] The inventive method is superior to known manufacturing methods. First, it is much more robust and can be easily upscaled. Second, less starting material is required and fewer by-products are generated. Third, the synthesis can be carried out directly in a low boiling solvent, so that after LC / QD synthesis, no solvent exchange to a low boiling solvent (e.g. toluene) is required. As a result, the manufacturing costs are significantly reduced, making LC / QDs accessible for many applications.
[0033] Luminescent crystals / quantum dots of formula (I): The method of the present invention provides LC / QDs with an average diameter of 2-50 nm, in particular 3-15 nm. The LC / QDs further have a narrow size distribution, as indicated by the small FWHM value of the emission peak.
[0034] In one embodiment, the present invention relates to an LC / QD of formula (I), where a=1, b=1, and c=3.
[0035] In one embodiment, the present invention relates to an LC / QD of formula (I), wherein M1 =Cs.
[0036] In one embodiment, the present invention relates to an LC / QD of formula (I), wherein M 2 = Pb.
[0037] In one embodiment, the present invention relates to an LC / QD of formula (I), wherein X is a combination of at least two elements selected from the group consisting of Cl, Br, and I.
[0038] In one embodiment, the present invention relates to an LC / QD of formula (I) selected from Cs1Pb1X3, in particular CsPbBr3, CsPbBr2I. This embodiment includes the corresponding molar mixtures of CsBr and PbBr2, or mixtures of CsI and PbBr2.
[0039] In a further embodiment, the present invention further comprises a doped material, i.e., 1 A part of M is replaced with another alkaline metal, or 2 In another embodiment, the LC / QD of formula (I) is a LC / QD in which a portion of X is replaced with another transition metal or rare earth element, or a portion of X is replaced with another halide.
[0040] In a further embodiment, the present invention provides a method for the preparation of a compound comprising the steps of: 1 SnX3, M 1 3Bi2X9,M 1 The LC / QDs of formula (I) are selected from GeX3.
[0041] The compounds of formula (I) include stoichiometric and non-stoichiometric compounds. The compounds of formula (I) are stoichiometric, b and c represent natural numbers; they are non-stoichiometric, b and c represent integers. In a further embodiment, the present invention relates to an LC / QD of formula (I), in which a portion of X is replaced with one or more anions selected from the group consisting of cyanide, thiocyanate, isothiocyanate, and sulfide. Exemplary embodiments include: M 1 a M 2b X 1 c’ X 2 c’’ (I-1) and wherein: M 1 , M 2 , a, b are as specified above; X 1 represents the specified halide; X 2 represents an anion selected from cyanide, thiocyanate, isothiocyanate, and sulfide; c'+c'' represents a real number between 3 and 9, and c' / c'' is greater than 0.9. Sulfides are 2-atoms and are therefore counted twice when calculating c''.
[0042] Exemplary embodiments of formula (I-1) include CsPbCl 2.9 CN 0.1 , CsSnBr2(SCN)1, Cs3Bi2Br 8.8 (NCS) 0.2 , and CsPbBr 0.43 I 2.43 S 0.07 Examples include:
[0043] Solid material: A suitable solid material provided in step (a) has an average particle size of at least 15 nm and a polydisperse size distribution, typically from 15 nm to 100 μm, more typically from 50 nm to 50 μm. The particle size of the solid material is determined by SEM, TEM or BET.
[0044] Moreover, such solid materials have a chemical composition that corresponds to the chemical composition of the desired LC / QDs. Thus, such solid materials have a mole M 1 , b moles M 2 , and c moles of X.
[0045] Such materials may be provided to the process of the invention by different methods, for example (a1), (a2) and (a3), as outlined below. The materials may be provided to step (b) continuously or discontinuously by known methods.
[0046] Wet synthesis process (a1): The preparation of solid materials according to formula (I) is known per se. The most common methods include wet synthesis processes, such as precipitation from a solvent-based or aqueous phase. The material may be provided to step (b) continuously or discontinuously by known methods.
[0047] This method may be considered to be "top-down": the solid starting material obtained by wet synthesis exhibits a polydisperse particle size distribution with an average particle size larger than 15 nm (measured by BET, SEM, or TEM), whereas the synthesized luminescent crystals exhibit a very narrow size distribution with an average size between 2 and 50 nm (see FIG. 1b). By following the method described herein, the average particle size and polydispersity of the starting material are reduced in order to obtain a narrow size distribution and particle size between 2 and 50 nm.
[0048] Dry synthesis processes in the gas phase (a2-1): Alternative methods for producing solid materials according to formula (I) include dry synthesis processes in the gas phase, in particular decomposition and pyrolysis processes, such as flame spray pyrolysis processes. The solid materials obtained by this process are typically smaller than (a1).
[0049] This method may be considered to be "top-down": the solid starting material obtained by dry synthesis exhibits a polydisperse particle size distribution with an average particle size larger than 15 nm (measured by BET, SEM, or TEM), whereas the synthesized luminescent crystals exhibit a very narrow size distribution with an average diameter between 2 and 50 nm (see FIG. 1b). Thus, at least a portion of the starting material is reduced in size.
[0050] Dry synthesis process by milling (a2-2): A further method for producing a solid material according to formula (I) includes dry milling of a precursor material. In this embodiment, the solid material is of formula aM 1 1X1 and M 2 b X (c-a) where the substituents are as defined above. For example, CsPbBr3, Cs4PbBr6 can be accessed by a corresponding molar mixture of the precursors CsI and PbBr2, or CsPbBr2I can be accessed by a corresponding mixture of the precursors CsBr and PbBr2. A dry milling process, for example using a pestle and mortar or involving stirred milling balls, then provides a dry crystalline material according to formula (I). This process can be considered as a solid-state reaction induced by milling.
[0051] In situ formation (a3): A further alternative for the solid material according to formula (I) is in situ formation, e.g., a solid-state reaction during the dispersion process. In this embodiment, the solid material is of formula aM 1 1X1 and M 2 b X (c-a) where the substituents are as defined above. For example, CsPbBr3, Cs4PbBr6 are available through a corresponding molar mixture of the precursors CsI and PbBr2, or CsPbBr2I is available through a corresponding mixture of the precursors CsBr and PbBr2. The crystalline material according to formula (I) is then formed during the dispersion process (i.e. in situ) by reaction of the two precursors of the solid material.
[0052] The above precursors are then obtainable by known methods, such as wet synthesis processes, dry synthesis processes, etc. The skilled person is in a position to select the appropriate precursors to obtain the luminescent crystals of formula (I). This method may also be considered "top-down" since the precursors used are larger than the resulting LC / QDs.
[0053] In one embodiment, the average particle size of the solid material (determined by BET, SEM or TEM) is at least 15 nm, preferably between 15 nm and 100 μm, more preferably between 50 nm and 50 μm.
[0054] In an advantageous embodiment, the solid material consists of a single composition having the same stoichiometry as the final LC / QDs of formula (I).
[0055] Step (b): Without being limited by theory, it is believed that upon dispersion of the starting materials in the liquid phase, a number of effects occur simultaneously or sequentially.
[0056] First, the solid material is uniformly distributed within the liquid phase.
[0057] Second, the solid material is contacted with a surfactant, which is believed to coat the material and stabilize it in the liquid phase.
[0058] Third, the particle size of the solid material is reduced. Without being limited by theory, it is believed that two mechanisms occur: (1) mechanical crushing / fragmentation of particles larger than the final LC / QD size, and (2) Ostwald ripening and sintering of particles smaller than the final LC / QD size, resulting in a monodisperse particle size distribution.
[0059] In certain embodiments, the average particle size of the solid starting material is at least 1.5 times (preferably at least 2 times, most preferably at least 5 times) greater than the average particle size of the correspondingly synthesized LC / QDs.
[0060] Liquid: As outlined above, the dispersion in step (b) is carried out in a liquid phase. Suitable liquids may be selected from (i) liquid surfactants, (ii) combinations of (liquid or solid) surfactants and solvents, (iii) combinations of (liquid or solid) surfactants, solvents and (liquid or solid) prepolymers or polymers, and (iv) combinations of (liquid or solid) surfactants and liquid prepolymers.
[0061] In embodiment (i), the liquid phase consists (or consists essentially) of a liquid surfactant. This embodiment is advantageous as it is a simple solvent-free system.
[0062] In embodiment (ii), the liquid phase consists (or consists essentially) of a combination of a (liquid or solid) surfactant and a solvent. This embodiment is advantageous as it allows the use of a solid surfactant.
[0063] In embodiment (iii), the liquid phase consists (or consists essentially) of a combination of (liquid or solid) surfactant, one or more solvents, and (liquid or solid) prepolymer or polymer. This embodiment is advantageous as it provides a composition that may be used directly to prepare intermediates as defined below.
[0064] In embodiment (iv), the liquid phase consists (or consists essentially) of the liquid prepolymer. This embodiment is advantageous as it provides a composition that is solvent-free and may be used directly to prepare intermediates as defined below.
[0065] Solvent: The term solvent is defined above. For the avoidance of doubt, the term solvent does not include surfactants or prepolymers.
[0066] Advantageously, the solvent is selected from the group of hydrocarbons (including linear, branched and cyclic hydrocarbons), aromatic hydrocarbons, ethers (including glycol ethers), esters, alcohols, ketones. Preferably, the solvent is selected from the group of linear and branched C 5~24 Preferably, the solvent is selected from the group of linear C 5~15 The alkyl group is selected from the group consisting of an alkane, and toluene.
[0067] In a further embodiment, the solvent exhibits a boiling point below 140° C., preferably below 120° C. An advantageous aspect of the method of the present invention is that it is possible to obtain LC / QDs at much lower temperatures compared to previous methods, such as those of Protesescu or Zhang mentioned above, both of which use synthesis methods between 140 and 200° C.
[0068] Prepolymer: The term prepolymer has been defined above. Advantageously, the prepolymer is selected from the group of acrylates, carbonates, sulfones, epoxies, vinyls, urethanes, imides, esters, furans, melamines, styrenes and silicones. Preferably, the prepolymer is selected from the group of acrylates, urethanes, styrenes. Particularly preferably, the prepolymer is selected from the group of acrylates.
[0069] Surfactants: A wide variety of surfactants may be used in the context of the present invention. The appropriate surfactant may be determined by repeated experimentation; its selection depends mainly on the nature of the polymer and solid material used in the next step. The surfactant may be selected from the classes of nonionic, cationic, zwitterionic and anionic surfactants. The combination of two or more surfactants to improve positive properties is known in the art; such surfactant combinations are also the subject of the present invention.
[0070] Nonionic surfactants include: maleic acid polymers such as poly(maleic anhydride-ortho-1-octadecene), polyamines, alkylamines (e.g., N-alkyl-1,3-propylene-diamines, N-alkyldipropylene-triamines, N-alkyltripropylene-tetraamines, N-alkylpolypropylene-polyamines), poly-(ethyleneimines), polyesters, alkyl esters (e.g., cetyl palmitate), alkyl polyglycol ethers (e.g., fatty alcohol polyglycol ethers having 3 to 25 ethoxy units (EO), e.g., Dehypon E124, and oxo alcohol polyglycol ethers), mixed alkyl / aryl polyglycol ethers, alkyl polyglucosides (APGs), fatty alcohols such as stearyl alcohol (e.g., Lorol C18™).
[0071] Nonionic surfactants further include polymeric ethoxylate and / or propoxylate (EO / PO) adduct surfactants, such as fatty alcohol alkoxylates, alcohol EO / PO adducts (including fatty alcohol EO / PO adducts, oxo alcohol EO / PO adducts), EO / PO block copolymers, ethylenediamine ethylene oxide-propylene oxide (EO / PO) block copolymers, end-capped (aliphatic) alcohol EO adducts and EO / PO adducts (e.g. butyl end-capped), esters of carboxylic acids, in particular EO / PO adducts and sorbitan esters (e.g. from the group SPAN).
[0072] Nonionic surfactants further include alkoxysilanes and their hydrolysis products.
[0073] Non-ionic surfactants further include alkyl phosphines, alkyl phosphine oxides (eg, trioctylphosphine oxide-TOPO), and alkyl thiols.
[0074] Nonionic surfactants further include alkyl esters of fatty acids (eg, cetyl palmitate, laurate, caprate).
[0075] A preferred class of non-ionic surfactants are the alkylimines, alkylamines, such as dioctylamine, oleylamine, octadecylamine, hexadecylamine.
[0076] Cationic surfactants include: alkyl ammonium halides, more specifically alkyl trimethyl ammonium halides such as cetyl trimethyl ammonium bromide, dialkyl dimethyl ammonium halides such as distearyl dimethyl ammonium chloride, trialkyl methyl ammonium halides such as trioctyl methyl ammonium chloride, diquaternary polydimethyl siloxanes.
[0077] Zwitterionic surfactants include: betaines such as caprylic acid glycinate, cocoamidopropyl betaine, and disodium cocoamphodiacetate.
[0078] Anionic surfactants include sulfates, sulfonates, phosphates, and carboxylates. Specific examples include the phosphate esters of alkyl ethers, ammonium lauryl sulfate, alkali lauryl sulfate, and related alkyl ether sulfates such as alkali laureth sulfate.
[0079] A preferred class of anionic surfactants are the carboxylates of fatty acids, such as the oleic, stearic, palmitic acid classes.
[0080] In a preferred embodiment, the surfactant is selected from the following list: SP 13300, SP 20000, SP 24000SC, SP 41000, SP540, BYK9077, Hypermer KD1-SO-(AP), Span65, Span80, Span85, Methoxy-ethoxy-ethoxy-acetic acid, oleylamine, oleic acid, stearic acid, poly(maleic anhydride-ortho-1-octadecene), and TOPO.
[0081] In a further preferred embodiment, the surfactant is selected from the following list: SP 13300, SP 20000, SP 24000SC, SP 41000, SP540, BYK9077, Hypermer KD1-SO-(AP), Span65, Span80, Span85, Methoxy-ethoxy-ethoxy-acetic acid, stearic acid, poly(maleic anhydride-ortho-1-octadecene), and TOPO, hexadecylamine, octadecylamine, dioctylamine.
[0082] In a further embodiment, the surfactant is selected from the group of anionic surfactants, cationic surfactants, nonionic surfactants, and zwitterionic surfactants comprising a non-polar end group selected from the group of alkyl or alkyl-ether chains having from 4 to 30, preferably from 6 to 24, and most preferably from 8 to 20 carbon atoms.
[0083] In a further embodiment, the surfactant has the formula RO-(CHO) m (C3H6O) n (wherein m and n are independently 0 to 10, but m+n>2, R is C 1~5 The surfactants are selected from the group of anionic surfactants, cationic surfactants, nonionic surfactants, and zwitterionic surfactants, with one or more chemical moieties selected from the group of alkyl ethers having a moiety where R is -alkyl.
[0084] In a further embodiment, the anionic surfactant has formula (II): R(OC n H2n ) q OCH2C(O)OH (II) wherein R is selected from monocarboxylic acids containing a polyether tail, represented by the formula: 1~5 -alkyl, q is an integer from 0 to 5, and n is an integer from 1 to 3. Five particularly preferred compounds of that class are [ka] where q is 0 to 4. This corresponds to compounds of formula (II) where R is methyl, n is 2, and q is an integer from 0 to 4. Particularly preferred compounds of that class are [ka] It is.
[0085] Dispersion treatment: Suitable dispersion treatments include dispersion methods involving milling balls. In a preferred embodiment, the dispersion method is ball milling, preferably using an agitated ball mill. In a preferred embodiment, the ball diameter is less than 5 mm, preferably less than 500 microns. In a further embodiment, the dispersion method is ball milling with a ball diameter of 10-1000 μm, preferably 20-500 μm. In a further embodiment, the dispersion method is ball milling with a specific power input per unit mass of suspension of at least 10 W / kg, preferably 100 W / kg, most preferably 1000 W / kg. In one further embodiment, the temperature of the suspension during the dispersion treatment is less than 140° C., preferably less than 120° C., most preferably less than 70° C. Surprisingly, it has been found that by using agitated milling balls, solid materials as defined above can be converted into LC / QDs with excellent optical properties (high quantum yield, small FWHM), providing LC / QDs with excellent properties and low reaction temperature. This is considered to be a significant advantage over known methods.
[0086] In a further embodiment of the method of the present invention the mass ratio of solid materials:liquid materials (solvent+prepolymer+surfactant) is in the range of 0.0001-0.5, preferably 0.0005-0.1, most preferably 0.001-0.05.
[0087] In a further embodiment of the process of the present invention the surfactant:solid material mass ratio is in the range 100-0.1, preferably 50-0.5, most preferably 20-1.
[0088] Post-treatment: In further embodiments, the as-synthesized LC / QDs may be subjected to post-treatment, for example as outlined in steps (b-2), (b-3), (b-4) and (b-5) below.
[0089] In one embodiment of such post-treatment, the halogen atom X of the synthesized LC / QD can be completely or partially replaced with other halogen atoms by anion exchange. For anion exchange (b-2), in particular, alkali halides such as NaI, KI, LiI, and lead halides such as PbI2 may be used. This allows fine tuning of the emission peak.
[0090] In a further embodiment of such post-treatment, two or more types of luminescent crystals of formula (I) are mixed. By mixing different types of luminescent crystals, i.e., by combining two suspensions of such luminescent crystals, the emission peak of the composition is adjusted. (b-5)
[0091] In a further embodiment, the compositions of the present invention may be purified from excess surfactant by diafiltration of the synthesized composition. (b-3)
[0092] In further embodiments, the solids content of the LC / QDs of the compositions of the invention may be increased by diafiltration or solvent evaporation of the synthesized compositions. (b-4)
[0093] In a second aspect, the invention relates to a composition in the form of a suspension, also called an "ink", and to uses thereof.Embodiments of the invention are described in more detail below.
[0094] The present invention therefore provides a composition in the form of a suspension comprising: (i) a luminescent crystal of formula (I) as described herein; (ii) a surfactant as described herein, except for oleylamine, oleic acid, and trioctylphosphine; (iii) any solvent as described herein; and (iv) any polymer or prepolymer as described herein. Such compositions are novel and may be obtained by the process of the present invention as described in the first aspect of the invention.
[0095] In one embodiment, the present invention provides a suspension whose quantum yield is greater than 20%, preferably greater than 50%, and most preferably greater than 70%.
[0096] In a further embodiment, the present invention provides a suspension wherein the FWHM of LC / QD for visible emission is less than 50 nm, preferably less than 40 nm, and most preferably less than 30 nm.
[0097] In a further embodiment, the present invention provides a suspension in which the FWHM of LC / QDs having an emission peak between 480-550 nm or 600-680 nm is less than 40 nm, preferably less than 30 nm, and most preferably less than 20 nm.
[0098] In a further embodiment, the present invention provides a suspension, wherein the FWHM of LC / QDs having an emission peak between 480-530 nm is less than 40 nm, preferably less than 30 nm, and most preferably less than 20 nm.
[0099] The amounts of components (i), (ii), (iii) and (iv) may vary over wide ranges and depend, among other things, on the intended use and the nature of the surfactant.
[0100] In one embodiment, the mass ratio of luminescent crystal (i):liquid materials (ii)+(iii)+(iv) is in the range of 0.0001 to 0.5, preferably 0.0005 to 0.3, and most preferably 0.001 to 0.1.
[0101] In a further embodiment, the mass ratio of surfactant (ii):luminescent crystal (i) is in the range 100-0.05, preferably 50-0.2, most preferably 20-1.
[0102] In a further embodiment, the concentration of the polymer or prepolymer ranges from 0.1 to 30% by weight, preferably from 0.5 to 20% by weight, most preferably from 1 to 10% by weight of the total composition.
[0103] As outlined above, components (i) and (ii) are essential, whereas components (iii) and (iv) are optional. Thus, the present invention relates to an ink comprising (i.e. comprising or consisting of): comprising components (i) and (ii), wherein (ii) is a liquid, and does not comprise (iii) and (iv); Contains components (i), (ii) and (iii) but not (iv); Contains components (i), (ii) and (iv) but not (iii); Contains components (i), (ii), (iii), and (iv).
[0104] In a further embodiment, the composition comprises components (i), (ii), (iii) and (iv), wherein component (ii) comprises an aromatic hydrocarbon, preferably toluene, and component (iv) comprises a cyclic olefin copolymer.
[0105] In a further embodiment, the composition comprises components (i), (ii), (iii) and (iv), wherein component (ii) comprises a linear alkane and / or an aromatic hydrocarbon, and component (iv) comprises a styrene copolymer and / or a styrene block copolymer.
[0106] Solventless ink: The present invention provides a composition comprising components (i), (ii) and (iv) in the form of a suspension as described herein, but free or essentially free of solvent (iii). In this embodiment, the mass ratio of LC / QD (i):liquid materials (prepolymer (iv) + surfactant (ii)) is preferably in the range of 0.0001-0.5, preferably 0.0005-0.3, most preferably 0.001-0.1. Such compositions may be referred to as solventless inks and are particularly suitable for supplying to manufacturers of intermediates or devices as described below.
[0107] Prepolymers that are particularly suitable for solventless inks include acrylates, epoxies, urethanes, silicones, styrenes. Again, the term prepolymer includes monomers and oligomers thereof. Preferably, the solventless ink comprises an acrylate.
[0108] An ink is considered to be solvent-free if it contains less than 10% by weight solvent, preferably less than 1% by weight.
[0109] In a further embodiment, the solventless ink further comprises a polymerization initiator, for example a radical photoinitiator, or a temperature sensitive radical initiator.
[0110] Concentrates: The present invention provides compositions in the form of suspensions as described herein, which are free or essentially free of solvent (iii), free or essentially free of prepolymer (iv), and surfactant (ii) is a liquid surfactant. In this embodiment, the mass ratio of surfactant (ii):LC / QD (i) is preferably in the range of 100-1, preferably 50-2, most preferably 20-10.
[0111] The inks described herein have many uses, and are particularly useful for converting blue light to white light using light emitting diodes (LEDs).
[0112] In a third aspect, the present invention relates to a solid polymer composition and its uses. The term solid polymer composition refers to an organic or inorganic polymer matrix containing LC / QDs as described herein. The following describes the aspects of the present invention in more detail.
[0113] In one embodiment, the present invention provides a solid polymer composition comprising: (i) LC / QDs as described herein; (ii) a surfactant as described herein, except for oleylamine, oleic acid, and trioctylphosphine; and (iii) a curing / solidifying polymer, preferably selected from organic polymers.
[0114] In a further embodiment, the organic polymer is preferably selected from the group of acrylate polymers, carbonate polymers, sulfone polymers, epoxy polymers, vinyl polymers, urethane polymers, imide polymers, ester polymers, furan polymers, melamine polymers, styrene polymers, and silicone polymers. Thus, the polymer preferably comprises repeat units of the prepolymers described herein. Furthermore, the polymer can be linear or crosslinked.
[0115] In a further embodiment, the organic polymer is preferably selected from the group of acrylate polymers, epoxy polymers, urethane polymers, styrene polymers, silicone polymers, and cyclic olefin copolymers. Thus, the polymer preferably comprises repeat units of the prepolymers described herein. Furthermore, the polymer can be linear or crosslinked.
[0116] In one embodiment, the organic polymer comprises a styrene copolymer and / or a styrene block copolymer, preferably a block copolymer of styrene and isoprene, a block copolymer of styrene, ethylene, and butene.
[0117] In one embodiment, the mass ratio of LC / QD:matrix (polymer + surfactant) in the solid polymer composition is in the range of 0.0001-0.1, preferably 0.0005-0.05, and most preferably 0.001-0.02.
[0118] In one embodiment, the surfactant:LC / QD mass ratio in said solid polymer composition is in the range of 100-0.05, preferably 50-0.2, and most preferably 20-1.
[0119] In a further embodiment, the quantum yield of the solid polymer composition of the present invention is higher than 20%, preferably higher than 50%, and most preferably higher than 70%.
[0120] In a further embodiment, the FWHM of the solid polymer composition of the present invention for visible emission is less than 50 nm, preferably less than 40 nm, and most preferably less than 30 nm.
[0121] In a fourth aspect, the present invention relates to an intermediate article comprising a sheet-like substrate coated with one or more layers, at least one of said layers being a functional layer, said functional layer comprising a solid polymer composition as described herein. Aspects of the present invention are described in further detail below.
[0122] In an advantageous embodiment, the functional layer converts blue light into white light.The invention therefore provides the use of the solid polymer composition for converting blue light into white light, in particular with light emitting diodes (LEDs) or in liquid crystal displays.
[0123] In a fifth aspect, the invention relates to novel devices / articles.Aspects of the invention are described in further detail below.
[0124] In one embodiment, the present invention provides a device selected from the group of electronic devices and optical devices, said device comprising a substrate and a functional layer; said functional layer comprises LC / QDs of formula (I) as described herein and a surfactant as described herein, except for oleylamine, oleic acid, and trioctylphosphine. Such a device may be selected from the group consisting of a display, a mobile device, a light emitting device, and a solar cell, in particular the device is a liquid crystal display device or a quantum dot LED (QLED).
[0125] In one embodiment, the present invention provides an article comprising a substrate and a coating, particularly a decorative coating, the coating comprising LC / QDs of formula (I) as described herein and a surfactant as described herein, except for oleylamine, oleic acid, and trioctylphosphine.
[0126] In a sixth aspect, the present invention relates to a method for producing a polymer composition as described herein, the method comprising steps known in the art except for using an ink as described herein as one or only starting material.
[0127] In a seventh aspect, the present invention relates to a method for producing an intermediate as described herein.Aspects of the present invention are described in further detail below.
[0128] The intermediate product according to the invention may be obtained by solution processing. This is considered to be a significant advantage since it allows all layers to be produced by simple techniques suitable for large area and continuous operation. The invention therefore provides a method for producing an intermediate product as described herein, said method comprising the steps of (e) providing a substrate and (f) depositing on said substrate a solid polymer composition as described herein, preferably by printing an ink as described herein, followed by drying and / or solidifying the coating.
[0129] In an eighth aspect, the invention relates to a method of manufacturing an electronic device as described herein.Aspects of the invention are described in further detail below.
[0130] The manufacture of devices starting from the above intermediate products is known per se, but has not yet been applied to the specific intermediate products of the present invention. EXAMPLES
[0131] The following examples are provided to further illustrate the present invention, without intending to limit the scope of the invention. Unless otherwise stated, all chemicals were purchased from Aldrich.
[0132] Example 1: Synthesis from solid materials obtained by precipitation methods
[0133] Cesium lead tribromide (CsPbBr3) was synthesized by mixing PbBr2 and CsBr under acidic conditions. 2 mmol of PbBr2 (0.731 g, 98% ABCR) was dissolved in 3 mL of concentrated HBr (48%, Alfa Aesar). 2 mmol of CsBr (0.426 g, 99.9% ABCR) was dissolved in 1 mL of H2O and added to the PbBr2 solution. A bright orange solid immediately precipitated from the solution. The solid was filtered, washed four times with pure EtOH, and dried under vacuum for 5 hours to give 1.12 g of pure orthorhombic CsPbBr3 (96.8% yield). This material does not exhibit any luminescence. SEM analysis showed that the average particle size ranged from 0.5 to 6 microns.
[0134] Dry CsPbBr3 powder was added to oleylamine (70%, Aldrich) (CsPbBr3:oleylamine=1:10) and toluene (>99.7%, Fluka). The final concentration of CsPbBr3 was 1%. The mixture was then dispersed by ball milling with yttrium-stabilized zirconia beads with a diameter of 200 microns at ambient conditions for 1 hour to obtain an ink with green luminescence. The absorption and luminescence properties of the ink in air-equilibrated solution in a 10 mm quartz cuvette were recorded using a Perkin Elmer Lambda 45 spectrophotometer and a Perkin Elmer LS50B spectrofluorometer equipped with a Hamamatsu R928 phototube, respectively. The ink was diluted with toluene until the absorbance value at the excitation wavelength was below 0.1.
[0135] The photoluminescence quantum yield of the above ink was 71%, with an emission peak centered at 507 nm. The FWHM of the emission was determined to be 19 nm. A solution of fluorescein (analytical reference grade, Aldrich) in 0.1 M NaOH was used as the photoluminescence quantum yield standard.
[0136] TEM analysis of the ink (Figure 2) showed the presence of cubic shaped particles with a very narrow particle size distribution.
[0137] For XRD analysis of the ink, the QDs were precipitated with acetonitrile and dried for analysis. Cubic CsPbBr3 was the dominant phase.
[0138] The above experiment was repeated, except that pure methyl methacrylate was used instead of toluene, and the final ink showed a slightly blue-shifted emission.
[0139] Example 2: Synthesis from solid materials obtained by flame spray pyrolysis
[0140] For the preparation of the CsPbBr3 precursor, 2.5 mmol of cesium acetate (0.48 g, ABCR) and 2.5 mmol of lead 2-ethylhexanoate (1.23 g, Strem) were added to 2-ethylhexane (Aldrich) and dissolved by heating the mixture at 150 °C for 1 h. After cooling to room temperature, 7.5 mmol of bromobenzene (1.18 g, Aldrich) was added to the mixture. The resulting solution was diluted 1:2 by mass with xylene. The precursor was delivered to a spray nozzle (9 mL min -1 , HNP Mikrosysteme, Micro Annular Gear Pump MZR-2900), dispersed with oxygen (9 lmin -1 , PanGas tech), premixed methane-oxygen flame (CH4: 1.2 lmin -1 , O2: 2.2 lmin -1 The off-gas was removed by a vacuum pump (Busch, Seco SV1040CV) at a pressure of approximately 20 m 3 h -1 The mixture was filtered through a glass fiber filter (Schleicher & Schuell) at 37° C. The resulting oxide powder was collected from the glass fiber filter. XRD analysis of the resulting powder confirmed its composition as CsPbBr3. SEM analysis showed that the average particle size was less than 500 nm.
[0141] CsPbBr3 powder was added to Span65 (Aldrich) (CsPbBr3:Span65=1:10) and toluene (>99.7%, Fluka). The final concentration of CsPbBr3 was 0.2%. The mixture was then dispersed by ball milling for 30 minutes at ambient conditions using yttrium-stabilized zirconia beads with a diameter of 50 microns to obtain an ink with green luminescence. The absorption and luminescence properties of the ink were recorded as shown in Example 1. The photoluminescence quantum yield of the above ink was 37% with an emission peak centered at 511 nm. The FWHM of the emission was determined to be 25 nm.
[0142] For XRD analysis of the ink, the QDs were precipitated with acetonitrile and dried for analysis. Cubic CsPbBr3 was the dominant phase.
[0143] Example 3: Synthesis from a solid material composed of a mixture of two different precursors
[0144] Commercial CsBr (99.9%, ABCR) and PbBr2 (98%, ABCR) powders were mixed in equal molar ratios to result in the net stoichiometric composition of CsPbBr3. The salt mixture was added to oleylamine (70%, Aldrich) (CsPbBr3:oleylamine=1:10) and toluene (>99.7%, Fluka). The final concentration of CsPbBr3 was 0.2%. The mixture was then dispersed by ball milling for 150 minutes at ambient conditions using yttrium-stabilized zirconia beads with a diameter of 50 microns to obtain an ink with green luminescence. The absorption and luminescence properties of the ink were recorded as shown in Example 1. The photoluminescence quantum yield of the above ink was 48% with an emission peak centered at 503 nm. The FWHM of the emission was determined to be 37 nm.
[0145] For XRD analysis of the ink, the QDs were precipitated with acetonitrile and dried for analysis. Cubic CsPbBr3 was the dominant phase.
[0146] Example 4: Synthesis from solid materials obtained by precipitation using different dispersion methods
[0147] Cesium lead dibromide iodide (CsPbBr2I) was synthesized by mixing PbBr2 and CsI from methyl sulfoxide (DMSO) solutions. 1 mmol of PbBr2 (0.367 g, 98% ABCR) was dissolved in 2 mL of DMSO (>99.7%, Acros). 1 mmol of CsI (0.259 g, 99.9%, Alfa Acer) was dissolved in 1 mL of DMSO and added to the PbBr2 solution. After adding 20 mL of toluene (99.7%, Fluka), a bright red solid immediately precipitated out of solution. The solid was filtered, washed four times with pure EtOH, and dried under vacuum for 5 h to give 0.58 g of pure orthorhombic CsPbBr2I (92.6% yield). This material does not show any luminescence.
[0148] 0.02 g of the resulting salt was placed in a 30 mL glass vial containing 9.78 g of tetradecane (99%, Aldrich), 0.2 g of oleylamine (70%, Aldrich), 10 g of yttrium stabilized zirconia beads with a diameter of 50 microns, and a 3 cm magnetic bar. The mixture was mixed at 1000 rpm and 120° C. for 4 hours. After cooling to room temperature, the ink was filtered through a 0.45 um PTFE filter and yellow luminescence was observed. The absorption and luminescence properties of the ink were recorded as shown in Example 1. The photoluminescence was characterized by an emission peak centered at 552 nm with a FWHM of the emission peak of 30 nm.
[0149] All further experiments below were performed by ball milling using similar processing parameters (LC / QD:surfactant ratio = 1:10, milling bead size = 50 microns, milling time = 30 min, LC / QD concentration in ink = 0.2%, filtered through a 0.45 μm PTFE syringe filter for optical characterization, optical characterization is the same as in Example 1).
[0150] [Table 1]
[0151] Example 10: Synthesis from solid materials obtained by dry milling
[0152] Cesium lead tribromide (CsPbBr3) was synthesized by milling PbBr2 and CsBr: 2 mmol of PbBr2 (0.731 g, 98% ABCR) and 2 mmol of CsBr (0.426 g, 99.9% ABCR) were milled with yttrium-stabilized zirconia beads (2 mm diameter) for 2 hours to obtain 1.08 g of pure orthorhombic CsPbBr3 (93.3% yield). This material did not exhibit any luminescence. SEM analysis showed the average particle size to be in the range of 0.5-6 microns.
[0153] Orange CsPbBr3 powder was added to oleylamine (70%, Aldrich) (CsPbBr3:oleylamine=5:1) and toluene (>99.7%, Fluka). The final concentration of CsPbBr3 was 1%. The mixture was then dispersed by ball milling with yttrium-stabilized zirconia beads with a diameter of 50 microns at ambient conditions for 1 hour to obtain an ink with green luminescence. The absorption and luminescence properties of the ink were recorded as shown in Example 1.
[0154] The photoluminescence quantum yield of the above ink was 85% with an emission peak centered at 502 nm. The FWHM of the emission was determined to be 19 nm.
[0155] The green releasing ink was then mixed with a 10% cyclic olefin copolymer (COC, TOPAS Advanced Polymers) solution in toluene, coated onto a glass substrate, and dried at 60°C for 15 min. After drying, the resulting optical properties of the film were measured with a spectrofluorometer equipped with an integrating sphere (Quantaurus Absolute PL Quantum Yield Measurement System C1134711, Hamamatsu). The photoluminescence quantum yield of the film was 80% with an emission peak centered at 502 nm. The FWHM was determined to be 19 nm.
[0156] Example 11: Tuning emission wavelength after synthesis
[0157] The solid CsPbBr3 material from Example 10 was added to oleylamine (70%, Aldrich) (CsPbBr3:oleylamine=2:1) and n-heptane (99%, Aldrich). The final concentration of CsPbBr3 was 1%. The mixture was then dispersed by ball milling with yttrium-stabilized zirconia beads with a diameter of 50 microns at ambient conditions for 1 hour to obtain an ink with green luminescence. The absorption and luminescence properties of the ink were recorded as shown in Example 1. The photoluminescence quantum yield of the above ink was 89% with an emission peak centered at 501 nm. The FWHM of the emission was determined to be 20 nm.
[0158] Cesium lead triiodide (CsPbI3) was synthesized by milling PbI2 and CsI: 2 mmol of PbI2 (0.922 g, 99%, Aldrich) and 2 mmol of CsI (0.519 g, 99%, ABCR) were milled with yttrium-stabilized zirconia beads (diameter 2 mm) for 2 h to give 1.387 g of pure orthorhombic CsPbI3 (yield 96.2%). This material did not show any luminescence.
[0159] Yellow CsPbI3 powder was added to oleylamine (70%, Aldrich) (CsPbBr3:oleylamine=2:1) and n-heptane (99%, Aldrich). The final concentration of CsPbI3 was 1%. The mixture was then dispersed by ball milling with yttrium-stabilized zirconia beads with a diameter of 50 microns for 3 hours at ambient conditions to obtain an ink with red luminescence. The absorption and luminescence properties of the ink were recorded as shown in Example 1, except that a solution of cresyl violet (Aldrich) in MeOH was used as the photoluminescence quantum yield standard. The photoluminescence quantum yield of the above ink was 61% with an emission peak centered at 674 nm. The FWHM of the emission was determined to be 48 nm.
[0160] Next, 1 mL of the green-emitting CsPbBr3 ink was mixed with 150 μl of the red-emitting CsPbI3 ink. The mixture immediately shifted emission wavelength to be centered at 529 nm, and was found to have a photoluminescence quantum yield of 58% and a FWHM of 21 nm. There was no trace of photoluminescence from the original CsPbBr3 ink (501 nm) and CsPbBrI3 ink (676 nm).
[0161] In further testing, 0.5 mL of the green-emitting CsPbBr3 ink was mixed with 1 mL of the red-emitting CsPbI3 ink. The mixture immediately shifted emission wavelength to be centered at 640 nm, with a photoluminescence quantum yield of 86% and a FWHM of 37 nm. Again, no trace of photoluminescence originating from the original CsPbBr3 ink (501 nm) and CsPbBrI3 ink (676 nm) was found.
[0162] Example 12: Solvent-free system
[0163] 0.5 g of the green releasing ink of Example 10 was mixed with 1 g of Permabond UV681 UV-curable adhesive (Permabond Engineering Adhesives). The solvent present in the green releasing ink was removed by heating the mixture at 80° C. for 90 minutes. The remaining material was then coated between two glass slides and UV cured for 30 seconds (UVACUBE 100, Honle UV Technology) into a solid polymer film. The optical properties of the resulting film were measured as in Example 10. The photoluminescence quantum yield of the film was 77% with an emission peak centered at 502 nm. The FWHM was determined to be 19 nm.
[0164] Example 13: Compositions with styrene block copolymers and solid polymer compositions
[0165] 0.5 g of the green release ink (CsPbBr3 ink) from Example 11 was mixed with 5 g of 10 wt% polystyrene-block-polyisoprene-block-polystyrene in toluene (Aldrich, 14 wt% styrene). The material was then coated onto a glass slide and cured at 60°C into a solid polymer film. The optical properties of the resulting film were measured as in Example 10. The photoluminescence quantum yield of the film was 84% with an emission peak centered at 501 nm. The FWHM was determined to be 20 nm.
[0166] 0.5 g of the green emission ink (CsPbBr3 ink) from Example 11 was mixed with 5 g of 10 wt % polystyrene-block-poly(ethylene-ran-butadiene)-block-polystyrene (Aldrich) in n-heptane. The material was then coated onto a glass slide and cured at 60° C. into a solid polymer film. The optical properties of the resulting film were measured as in Example 10. The photoluminescence quantum yield of the film was 83% with an emission peak centered at 501 nm. The FWHM was determined to be 20 nm. Examples of embodiments of the present invention are listed below. [1] A method for producing a luminescent crystal having a diameter of 2 to 50 nm, the luminescent crystal being selected from a compound of formula (I): M 1 a M 2 b X c (I) During the ceremony: M 1 represents one or more alkali metals selected from Cs, Rb, K, Na, and Li; M 2 represents one or more metals selected from the group consisting of Ge, Sn, Pb, Sb, and Bi; X represents one or more halides selected from the group consisting of Cl, Br, and I; a represents 1 to 4; b represents 1 to 2; c represents 3 to 9; The method comprises the steps of: (a) providing a solid material, the solid material comprising: (i) a moles of M1 , b moles M 2 and c moles of X, and (ii) an average particle size of at least 15 nm, and typically a polydisperse size distribution of from 15 nm to 100 μm; (b) dispersing the material in the presence of a liquid, the liquid being selected from (i) a liquid surfactant, (ii) a combination of a surfactant and a solvent, (iii) a combination of a surfactant, a solvent, and a prepolymer or polymer, and (iv) a combination of a surfactant and a liquid prepolymer, the dispersion being effected by agitated milling balls. A method comprising: [2] The dispersion in step (b) is produced by agitated milling balls with ball diameters between 10 and 1000 μm; and / or caused by a specific power input of at least 100 W / kg per unit mass of the suspension; and / or 2. The method of claim 1, which occurs at a temperature of less than 120°C. [3] The light-emitting crystal is Cs 1 Pb 1 X 3 The method according to item 1 or 2, wherein the compound is selected from the group consisting of: [4] 4. The method according to any one of items 1 to 3, wherein the solvent is selected from the group consisting of aliphatic hydrocarbons (including straight chain, branched chain, and cyclic hydrocarbons), aromatic hydrocarbons, ethers (including glycol ethers), esters, alcohols, and ketones. [5] 5. The method according to any one of items 1 to 4, wherein the surfactant is selected from the group consisting of nonionic surfactants, anionic surfactants, cationic surfactants, and zwitterionic surfactants. [6] 6. The method according to any one of items 1 to 5, wherein the prepolymer is selected from the group of acrylates, carbonates, sulfones, epoxies, vinyls, urethanes, imides, esters, furans, melamines, styrenes, and silicones, in particular acrylates, urethanes, styrenes, and silicones. [7] In step (a), the solid material is Obtained by dry synthesis processes, including gas phase reactions and dry milling; or Obtained by wet synthesis processing; or The method according to any one of items 1 to 6, wherein the cation exchanger is formed in situ by stoichiometric reaction of two or more precursors corresponding to the net stoichiometric composition of formula (I). [8] The dry synthesis processes are gas phase processes, including decomposition and pyrolysis processes, such as flame spray pyrolysis processes; The wet synthesis process is a precipitation process from a solvent-based or aqueous phase; 8. The method according to claim 7, wherein the in situ formation occurs by ball milling the starting materials in the presence of a surfactant and, optionally, a solvent, and / or a liquid prepolymer, and / or a dissolved solid polymer. [9] the mass ratio of solid materials:liquid materials (solvent + surfactant) is in the range of 0.0001 to 0.5; and / or 9. The method according to any one of items 1 to 8, wherein the mass ratio of surfactant:solid material is in the range of 100 to 0.1.
[10] replacing one or more halogen atoms X of the synthesized luminescent crystal with other halogen atoms by anion exchange; and / or Combining two or more types of luminescent crystals of formula (I) The method according to any one of items 1 to 9, further comprising:
[11] (i) a luminescent crystal of formula (I) having a diameter of 2 to 5 nm according to item 1 or 3; (ii) a surfactant selected from the group of nonionic surfactants, anionic surfactants, cationic surfactants, and zwitterionic surfactants, excluding oleylamine, oleic acid, and trioctylphosphine; (iii) any solvent, preferably selected from the group of aliphatic hydrocarbons (including straight chain, branched chain, and cyclic hydrocarbons), aromatic hydrocarbons, ethers (including glycol ethers), esters, alcohols, ketones; (iv) any polymer or prepolymer, preferably selected from the group of acrylate, epoxy, urethane, styrene, silicone, and cyclic olefin copolymers; 1. A composition in the form of a suspension comprising:
[12] The mass ratio of the luminescent crystal (i):liquid material (ii)+(iii)+(iv) is in the range of 0.0001 to 0.5; and / or the mass ratio of surfactant (ii):luminescent crystal (i) is in the range of 100 to 0.05; and / or Item 12. The composition according to item 11, wherein the concentration of the polymer or prepolymer is in the range of 0.1 to 30% by weight of the total composition.
[13] the surfactant is selected from the group of anionic surfactants, cationic surfactants, nonionic surfactants, and zwitterionic surfactants; and 13. The composition according to item 11 or 12, wherein the surfactant comprises a non-polar end group selected from the group of alkyl or alkyl-ether chains having from 4 to 30 carbon atoms.
[14] does not contain a solvent (iii); 14. The composition according to any one of items 11 to 13, wherein the mass ratio of LC / QD(i):liquid materials (prepolymer (iv)+surfactant (ii)) is preferably in the range of 0.0001 to 0.5.
[15] The surfactant (ii) is a liquid surfactant and is free of the solvent (iii) and the prepolymer (iv); Surfactant (ii): The mass ratio of LC / QD (i) is in the range of 100 to 1; The composition according to any one of items 11 to 14.
[16] (i) a luminescent crystal of formula (I) having a diameter of 2 to 50 nm according to item 1 or 2; (ii) a surfactant selected from the group of nonionic surfactants, anionic surfactants, cationic surfactants, and zwitterionic surfactants, excluding oleylamine, oleic acid, and trioctylphosphine; (iii) a cured / hardened polymer, preferably selected from the group of acrylate polymers, epoxy polymers, urethane polymers, styrene polymers, silicone polymers, and cyclic olefin copolymers; and 1. A solid polymer composition comprising:
[17] the mass ratio of LC / QD:matrix (polymer + surfactant) is in the range of 0.0001–0.1; and / or The surfactant:LC / QD mass ratio is in the range of 100 to 0.05; 17. A solid polymer composition according to item 16.
[18] 18. An intermediate product comprising a sheet-like substrate coated with one or more layers, at least one of said layers being a functional layer, said functional layer comprising the composition according to item 16 or 17.
[19] Item 19. The intermediate product of item 18, wherein the functional layer converts blue light into white light.
[20] A device selected from the group of electronic devices and optical devices, the device comprising a substrate and a functional layer; the functional layer comprising LC / QDs of formula (I) according to item 1 or 3 and a surfactant according to any one of items 1, 5 or 13; Device.
[21] 21. The device according to item 20, which is selected from the group consisting of a display, a mobile device, a light-emitting device, and a solar cell, in particular an LCD display or a quantum dot LED (QLED).
[22] An article comprising a substrate and a coating, in particular a decorative coating, said coating comprising LC / QDs of formula (I) according to item 1 or 3 and a surfactant according to any one of items 1, 5 or 13.
[23] (a) providing a substrate; (b) depositing a solid polymer composition according to item 16 or 17 on said substrate, preferably by coating or printing with a composition according to any one of items 11 to 15, followed by drying and / or solidification; 20. A method for producing an intermediate according to item 18 or 19, comprising:
[24] Use of a composition according to any one of items 11 to 15 for producing an intermediate according to item 18 or 19; or for producing an apparatus according to item 20 or 21; or for producing an article according to item 22.
[25] 18. Use of a composition according to item 16 or 17 for converting blue light into white light, in particular in light emitting diodes (LEDs) or liquid crystal displays.
Claims
1. (i) a luminescent crystal; (ii) a surfactant selected from the group of nonionic, anionic, cationic, and zwitterionic surfactants, including nonionic surfactants; (iii) a cured / solidified crosslinked polymer selected from the group of acrylates; Including, The luminescent crystal is selected from compounds of formula (I): M 1 a M 2 b X c (I) During the ceremony: M 1 represents one or more alkali metals selected from Cs, Rb, K, Na, and Li; M 2 represents one or more metals selected from the group consisting of Ge, Pb, Sb, and Bi; X represents one or more halides selected from the group consisting of Cl, Br, and I; a represents 1; b represents 1; c represents 3; A solid polymer composition, wherein the luminescent crystals have an average diameter of 2-50 nm, a size distribution as indicated by the FWHM value of less than 30 nm peak for visible emission, and an aspect ratio in all three orthogonal dimensions (longitudinal:shortitudinal) of 1-2.
2. 2. The solid polymer composition of claim 1, wherein the weight ratio of said surfactant (ii): said luminescent crystal (i) is in the range of 20 to 0.
05.
3. 3. The solid polymer composition according to claim 1 or 2, wherein said surfactant (ii) is selected from non-ionic surfactants.
4. the mass ratio of the luminescent crystal:matrix (crosslinked polymer + surfactant) is in the range of 0.0001 to 0.1; and / or the mass ratio of the surfactant to the luminescent crystal is in the range of 20 to 0.2; The solid polymer composition of claim 1.
5. 13. An article comprising a sheet-like substrate coated with one or more layers, at least one of said layers being a functional layer, said functional layer comprising the composition of claim 1.
6. The article of claim 5 , wherein the functional layer converts blue light to white light.
7. 13. An apparatus selected from the group of electronic devices and optical devices, the apparatus comprising a substrate and a functional layer; the functional layer comprising the composition of claim 1.
8. 8. The device of claim 7, selected from the group consisting of a display, a mobile device, a light emitting device, and a solar cell.
9. An article comprising a substrate and a coating, the coating comprising the composition of claim 1.
10. 8. The device of claim 7, selected from the group consisting of an LCD display and a quantum dot LED.
11. 1. A method for producing a solid polymer composition, the method comprising: (a) providing a composition, the composition comprising: (i) a luminescent crystal; (ii) a surfactant selected from the group of nonionic, anionic, cationic, and zwitterionic surfactants, including nonionic surfactants; (iii) a cured / solidified crosslinked polymer selected from the group of acrylates; Including, The luminescent crystal is selected from compounds of formula (I): M 1 a M 2 b X c (I) During the ceremony: M 1 represents one or more alkali metals selected from Cs, Rb, K, Na, and Li; M 2 represents one or more metals selected from the group consisting of Ge, Pb, Sb, and Bi; X represents one or more halides selected from the group consisting of Cl, Br, and I; a represents 1; b represents 1; c represents 3; providing a composition, wherein the luminescent crystals have an average diameter between 2 and 50 nm, a size distribution as indicated by the FWHM value being less than 50 nm with a peak for visible emission, and an aspect ratio in all three orthogonal dimensions (longitudinal:shortitudinal) being between 1 and 2; (b) drying and / or solidifying the composition; A method comprising:
12. The method according to claim 11, wherein the surfactant (ii) is selected from the group of non-ionic surfactants.
13. 1. A method of making an article comprising a sheet-like substrate coated with one or more layers, at least one of the layers being a functional layer, the method comprising: (a) providing a sheet-like substrate; (b) depositing a functional layer on said substrate by coating or printing said composition as defined in claim 11 followed by drying and / or solidification. A method comprising:
14. The method of claim 13 , wherein the functional layer converts blue light to white light.
15. A method for manufacturing a device selected from the group of electronic devices and optical devices, the device comprising a substrate and a functional layer; the functional layer comprising a light-emitting crystal and a surfactant, the method comprising: (a) providing a substrate; (b) depositing a functional layer on said substrate by coating or printing said composition as defined in claim 11 followed by drying and / or solidification. A method comprising:
16. The method of claim 15 , wherein the device is selected from the group consisting of a display, a mobile device, a light emitting device, and a solar cell.
17. 1. A method for making an article comprising a substrate and a coating, the coating comprising a luminescent crystal and a surfactant, the method comprising: (a) providing a substrate; (b) depositing a coating on said substrate by coating or printing said composition as defined in claim 11 followed by drying and / or solidification. A method comprising:
18. 20. The method of claim 17, wherein the article is selected from the group consisting of an LCD display and a quantum dot LED.
Citation Information
Patent Citations
Luminescent material that emits light in the visible or near-infrared region
JP2009530488A
Semiconductor nanoparticle-based materials used in light-emitting diodes, optoelectronic displays, etc.
JP2014523634A
Composition for forming optical layer, and optical film
JP2015113360A
Composition for forming optical layer, and optical film
JP2015113361A
Improving quantum yield using highly reflective materials
JP2015522668A